2011
DOI: 10.1002/ejoc.201100759
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereocontrolled Synthesis of (Z)‐α‐(Phenylseleno)sulfinyl and ‐sulfonyl Alkenes via Sulfenic Acids, and a Study of their Reactivity

Abstract: Keywords: Sulfur / Selenium / Sulfenic acids / Alkenes / Michael addition A general procedure for the synthesis of α-(phenylseleno)-sulfinyl and -sulfonyl alkenes has been described. 1-(Phenylseleno)ethenyl sulfoxides were prepared by the syn-addition of in situ-generated sulfenic acids on to the triple bond of suitably substituted (phenylseleno)acetylenes. 1-(Phenylseleninyl)ethenyl sulfones were obtained by further oxidation of their sulfinyl analogues. The mild conditions of the sulfenic acid/(phenylseleno)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Further increasing the reaction temperature raised the yield of 3 aa to 73 % (Table 1, entry 4). A literature survey revealed that a brief study was carried out on thermolysis of β‐sulfinyl ester to emphasize the influence of carboxylate group in the sulfenic acid formation via trapping the sulfenic acid with selected alkynes [10d–h,12] . However, to the best of our knowledge, the comprehensive study exploring the synthetic utility of various β‐sulfinyl esters with a wide range of alkynes and detailed mechanistic studies has not been realized yet.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing the reaction temperature raised the yield of 3 aa to 73 % (Table 1, entry 4). A literature survey revealed that a brief study was carried out on thermolysis of β‐sulfinyl ester to emphasize the influence of carboxylate group in the sulfenic acid formation via trapping the sulfenic acid with selected alkynes [10d–h,12] . However, to the best of our knowledge, the comprehensive study exploring the synthetic utility of various β‐sulfinyl esters with a wide range of alkynes and detailed mechanistic studies has not been realized yet.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleophilicity of organic sulfenic acids has been utilized in synthetically useful routes toward sulfones, sulfoxides and alkenes, and forms the basis for their reaction chemistry with 7-chloro-4-nitrobenzo-2oxa-1,3-diazole for spectroscopic protein -SOH detection [15][16][17][18]. Lone electron pairs on the -SOH oxygen provide a-effect sulfur nucleophilicity, and the potential for oxygen nucleophilicity has also been documented [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic Procedures: The starting sulfoxides 3,3′,3″‐[(2,4,6‐triethyl‐1,3,5‐benzenetriyl)tris(methylenesulfinyl)]trispropanoic acid 1,1′,1″‐trimethyl ester 4 10a,10c and 3‐(phenylsulfinyl)propanoic acid methyl ester 7 10b were synthesized following already published methods.…”
Section: Methodsmentioning
confidence: 99%